DETERMINATION OF SELECTION CRITERIA FOR GRAIN YIELD IN CLIMATE RESILIENT SMALL MILLET CROP KODO MILLET (Paspalum scrobiculatum L.) - ABHINAV SAO,; PREETI SINGH,; PRAFULL KUMAR, (The Bioscan, 2024)
Association and path coefficient analysis has been conducted in twenty seven breeding lines of climate resilient crop Kodo millet to fix the selection criteria for grain yield. Grain weight showed positive and significant phenotypic inter relationship with fodder weight (rp =0.843), days to maturity (rg =0.843), panicle length (rp =0.285) and days to 50% flowering (rg =0.214) suggesting that these are the major yield contributing traits. While, path coefficient analysis showed plant height (0.192), number of panicles per plant (0.176), number of tillers per plant (0.087) and fodder weight (0.002) had positive direct effect whereas, days to maturity (-0.060) showed direct negative effect on grain yield of kodo millet. Thus, the correlation analysis showed fodder weight, panicle length, number of tillers per plant, plant height, and days to 50% flowering are the important yield components that can be fixed as selection criteria for improvement in grain yield of kodo millet.